Macular Corneal Dystrophy in an Adolescent Managed with Deep Anterior Lamellar Keratoplasty - Giri, Puspa; Bajracharya, Leena; Ranabhat, Sudha (Nepalese Journal of Ophthalmology, 2022)
Introduction: Macular corneal dystrophy (MCD) is a rare autosomal recessive stromal dystrophy. The prevalence of inherited diseases varies in different communities. It is not commonly observed in Nepal. Case: A 14-year male presented with bilateral gradual and painless blurred vision with photophobia of three years duration. Cornea of both eyes showed focal grayish opacities in anterior and mid stroma with intervening stromal haze. There was no history of consanguinity in the family. Anterior segment ocular coherence tomography showed thinning of cornea and deposits in corneal stroma. Macular corneal dystrophy was the clinical diagnosis and the patient underwent deep anterior lamellar keratoplasty in the right eye. Histopathological examination and histochemical staining with Alcian Blue supported the diagnosis. Conclusion: Significant improvement in vision was observed in the operated eye. MCD may be present in communities without evidence of consanguinity. It can cause visual impairment at an early age. Timely intervention improves vision and quality of life.